(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, pedagogical and psychological studies were conducted in higher education institutions in the Republic of Uzbekistan, and modern educational methods concepts of innovation, innovative education process, pedagogical innovation, management processes are high considered on the basis of educational institution. The main goal is to study innovative approaches in the formation of pedagogical and psychological methods in the higher education system psychological, methodological, philosophical literature, scientific approaches to innovation management the educational institution was analyzed and strategies were developed regarding the educational model and improvement was determined.